Seasonal and Land Type Based Soil Chemical and Nutrient Status in Agricultural Lands of Coastal District, Bagerhat, Bangladesh - Real, Md. Khalid Hassan; Mia, Md. Younus; Kumar, Utpol; Khanam, Natasha (International Journal of Environment, 2018)
The present study investigated the land type based seasonal status of agricultural topsoil chemical properties at Bagerhat district, Bangladesh. Because of relief and seasonal effect we hypothesized the changes of soil nutrient and chemical properties in topsoil. Composite soil samples were collected from fifteen purposive sampling points in pre-monsoon and post-monsoon period of 2016-2017. Soil digestion and analysis were performed following standard procedures. Topsoil pH was strongly alkaline to slightly alkaline (8.02-7.85) in pre-monsoon and post-monsoon with a significant variation. Seasonal OM status was below the optimum level (MHL). Considering the above issues present study suggests to avoiding excessive use of chemical fertilizer and encourages organic fertilizer for sustainable management of these agricultural lands.